(3aJM HjJ GdebOSs - (3TYHGf, Mdej Ydjs ((3HjQhJ, dHfGfs (3OGQ GdcJH GdYdejIs, 1993)
(3ef XdGe GdLGgdjI hGdTQc, Edi fhQ GdMb hGdEjeGf hGdJhMjO(B. (3ef eLJeY aGSO, Edi eLJeY YGOd WGgQ(B. (3ef JTQPe hJbGJd hJSdW Edi hMOI hJVGef hJYGhf(B. (3Jdc gj hUaGJ GdESdGe GdPj OYG Edjg eMeO Hf YHO Gddg QShd Gddg Udi Gddg Ydjg hSde HhMj ef QqH GdYGdejf(B. (3hHGdYhOI dYfGhjf gPg GdSdSdI fLO CfgG bOeJ TQMkG JGQjNjkG eaUdkG jYQV dcd GdCMOGK GdJj hbYJ aj gPg GdeYGQc hGdaJhMGJ hddaQb GdeJbGJdI, hdYOO GdTgOGA, hdCge GdbGOI GdYScQjjf GdeTGQcjf, hddBjGJ GdJj fRdJ HgPg GdeYGQc, hPdc cdg LGA HCSdhH Sgd heHSW jLeY eG Hjf GdSQO GdbUUj hGdehYXI GdJQHhjI(B. (3hgPg GdeYGQc(B: (3ZRhI HOQ GdcHQi, eYQcI CMO, ZRhI GdCMRGH (B((3eYQcI GdNfOb(B)(3, ZRhI Hfj GdeUWdb, UdM GdMOjHjI, aJM NjHQ, SQjI eDJI, aJM ecI, ZRhI Mfjf, ZRhI JHhc, SbhW OheI GdLfOd, jhe GdjeGeI (B((3MQH GdQOI(B)(3, aJM GdMjQI, eYQcI GdjQehc, aJM OeTb, eYQcI GdHhjH, eYQcI GdbGOSjI, eYQcI CLfGOjf, aJM HjJ GdebOS, aJM GdeOGFf (B((3eYQcI LdhdGA(B)(3, SbhW aGQS, aJM eUQ, aJM eUQ, aJM fgGhfO(B-(3aJM GdeZQH hTeGd EaQjbjG, aJM GdCfOdSs
(3GdeMJhjGJ (B: (3HYO GdjQehc (B- (3MeU hTeGd ShQjI (B- (3aJM GdLRjQI (B- (3aJM HjJ GdebOS (B- (3WGYhf YehGS (B- (3aJM bjSGQjIs
Keywords: (3GdaJhMGJ GdESdGejIs